Hand Flexibility Assessment System Study Based on Pneumatic Actuation and Sensing - XIA, Yuanhao; GAO, Ting; WANG, Wanzhu; WANG, Yalan; CHEN, Shiqi; ZHANG, Yue; CHEN, Xinyuan (Rehabilitation Medicine, 2025)
ObjectiveTo develop a hand flexibility assessment system based on pneumatic actuation and sensing, and validate its accuracy and reliability. The system aims to provide a scientific basis for solving the problem of hand flexibility assessment and developing hand rehabilitation training plans.MethodsA pneumatic-driven assessment system consisting of pneumatic actuation modules, circuit boards, data feedback modules, and human-computer interaction modules is designed. The system uses air pressure as a quantitative indicator to assess hand flexibility. Based on the data collection needs of patients with varying degrees of hand dysfunction, four impedance evaluation modes with different intensities (mild, moderate, severe, and very severe) are designed. The soft actuator produces unilateral bending or relaxation through air inflation and deflation. During multiple finger flexions by the user, an opposing effect is generated between the user and the system. The air pressure inside the soft actuator is recorded in real time, providing data for hand flexibility assessment. Hand flexibility is quantified by combining the Brunnstrom hand function stage scale and the Total Active Motion (TAM) assessment method. Healthy subjects' test data are recorded and used as a template. The air pressure data of eight patients with hand dysfunction are collected for hand flexibility evaluation and compared with the results of three attending physicians from a rehabilitation center to verify the system’s accuracy in assessing hand flexibility.ResultsThe average air pressure change was maintained around 10 kPa for healthy subjects performing group impedance flexion tests. In 10 repeated experiments, the standard deviations of test results for the four intensity levels (mild, moderate, severe, very severe) were 0.37535, 0.27961, 0.39354, and 0.32010, respectively. During group impedance extension tests, the average air pressure change was maintained around 6 kPa, with standard deviations for the four intensity levels of 0.40442, 0.26102, 0.22012, and 0.13050, respectively, in 10 repeated experiments. For patients 1 and 2, based on the Brunnstrom evaluation scale, their finger recovery stages were determined to be Stage I and Stage II, respectively. For patients 3 and 4, the air pressure change was around 1 kPa. Patient 3 demonstrated better finger flexibility than patient 4. Patients 5 to 8 were evaluated using the TAM method, and patient 8 was classified with good hand flexibility, while the others were rated as poor.ConclusionThe system shows high accuracy and reliability in assessing hand flexibility and has the potential to replace rehabilitation physicians in quantitatively evaluating hand flexibility.